How 25 years of psychosocial research has contributed to a better understanding of the links between depression and diabetes. Issue 3 (24th January 2020) - Pouwer, F.; Schram, M. T.; Iversen, M. M.; Nouwen, A.; Holt, R. I. G.
Abstract: This narrative review of the literature provides a summary and discussion of 25 years of research into the complex links between depression and diabetes. Systematic reviews have shown that depression occurs more frequently in people with type 1 or type 2 diabetes compared with people without diabetes. Currently, it remains unclear whether depression is also more common in people with impaired glucose metabolism or undiagnosed type 2 diabetes compared with people without diabetes. More prospective epidemiological research into the course of depression and an exploration of mechanisms in individuals with diabetes are needed. Depression in diabetes is associated with less optimal self‐care behaviours, suboptimal glycaemic control, impaired quality of life, incident micro‐ and macrovascular diseases, and elevated mortality rates. Randomized controlled trails concluded that depression in diabetes can be treated with antidepressant medication, cognitive–behavioural therapy (individual, group‐based or web‐based), mindfulness‐based cognitive therapy and stepped care. Although big strides forward have been made in the past 25 years, scientific evidence about depression in diabetes remains incomplete. Future studies should investigate mechanisms that link both conditions and test new diabetes‐specific web‐ or app‐based interventions for depression in diabetes. It is important to determine whether treatment or prevention of depression prevents future diabetes complications and lowers mortality rates. What's new?: By 1995, a few epidemiological studies had concluded that depression was more common in people with diabetes than in those without. However, intervention studies were lacking and longitudinal studies were scarce. Over the past 25 years, research has confirmed the bidirectional relationship between depression and type 2 diabetes. Depression in diabetes impairs quality of life and is associated with less effective self‐management, a higher risk of diabetes complications and higher mortality rates. Depression in diabetes can be treated effectively with psychological and pharmacological therapy. Awareness of depression in people with diabetes should be raised and adequate mental health care should be available to treat depression. Future studies should elucidate the biological and behavioural mechanisms that link depression and diabetes and test the long‐term effects of treatment.